Nahdlatul Ulama, Education, and Da'wah: Tuan Mukhtar Muda Nasution's Contribution in South Tapanuli - Muallim Lubis (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article aims to analyze the contribution of Tuan Mukhtar Muda Nasution to the Nahdlatul Ulama (NU) organization, education, and da'wah, especially in the South Tapanuli region, North Sumatra. In the midst of Tuan Mukhtar’s achievement, researchers have not mentioned much about his contribution. He is also not well known within the NU organization and the wider community in North Sumatra. This study uses a social history approach with the main source coming from the autobiography of Tuan Mukhtar Muda Nasution and other books he has written such as Sejarah Singkat Nahdlatul Ulama and supported by data from interviews with his friends and students. The results of this study indicate that Tuan Mukhtar was an educated man from the Mandailing tribe, who studied at the intellectual center of the early 20th-century Sunni tradition in the land of the Hijaz. In North Sumatra, Tuan Mukhtar is an icon of Islamic religious education, especially among pesantren (Islamic boarding schools). In Nahdlatul Ulama in North Sumatra, he was once the Mustasyar of PBNU and Syuriah of PWNU of North Sumatra. As for the field of da'wah, he is highly appreciated because he is widely known as a cleric who contributed to Islam in South Tapanuli. This study presents a broader elaboration of Tuan Mukhtar based on new and reliable sources.Artikel ini bertujuan untuk menganalisis kontribusi Tuan Mukhtar Muda Nasution terhadap organisasi Nahdlatul Ulama (NU), pendidikan, dan dakwah, khususnya di wilayah Tapanuli Selatan, Sumatra Utara. Di tengah pencapaian Tuan Mukhtar, para peneliti belum banyak meneliti tentang kontribusinya. Ia juga kurang dikenal baik dalam organisasi Nahdlatul Ulama dan masyarakat luas di Sumatera Utara. Studi ini menggunakan pendekatan sejarah sosial dengan sumber utama berasal dari autobiografi karya Tuan Mukhtar Muda Nasution dan buku-buku lain yang ditulisnya seperti Sejarah Singkat Nahdlatul Ulama, serta didukung oleh data wawancara dengan para sahabat dan murid-muridnya. Hasil penelitian ini menunjukkan bahwa Tuan Mukhtar adalah seorang terpelajar dari suku Mandailing, yang belajar di pusat intelektual dari tradisi Sunni awal abad ke-20 di tanah Hijaz. Di Sumatra Utara, Tuan Mukhtar merupakan ikon tokoh pendidikan agama Islam, terkhusus di kalangan pesantren. Dalam Nahdlatul Ulama di Sumatera Utara, ia pernah menjabat sebagai Mustasyar PBNU dan Syuriah PWNU Sumatera Utara. Adapun dalam dunia dakwah, ia sangat dihargai sebab dikenal luas sebagai ulama yang berkontribusi terhadap Islam di Tapanuli Selatan. Studi ini menyajikan elaborasi yang lebih luas dari Tuan Mukhtar berdasarkan sumber baru dan tepercaya.